Aortic root reinforcement in aortic valve endocarditis with annular abscess: The Calamari procedure. Issue 7 (21st April 2022) - Petrov, Asen; Diab, Abdel‐Hannan; Taghizadeh‐Waghefi, Ali; Wilbring, Manuel; Alexiou, Konstantin; Matschke, Klaus Erhard; Tugtekin, Sems‐Malte; Kappert, Utz
Abstract: Treatment of infective endocarditis can often prove challenging due to its wide range of anatomical presentations. When complicated by an aortic root abscess, patients may require extensive root surgery, which on its own leads to a worse outcome. We present our experience with a surgical technique for reinforcing the aortic annulus with a ring from a Dacron aortic prosthesis placed in the left ventricular outflow tract to avoid the need for root replacement procedures or patch closures of the defect. The technique described in this paper provides a viable alternative to the standard techniques used for the treatment of annular abscesses in aortic valve endocarditis. Due to the relative simplicity and ease of use, this approach may present a means of reducing operation time and possibly postoperative complications of this severe condition.